“Being on the same boat”: PIBID AND TEACHING PRACTICUM AS ENHANCEMENT FOR a TEACHER EDUCATORS’ LEARNING - EL Kadri, Michele Salles (Revista X, 2015)
Research on PIBID indicates it has fostered changes in the way participants are becoming teachers (CASTELA, 2013b; MATEUS; EL KADRI; SILVA, 2013; RIBEIRO; CASTELA; JUSTINA, 2013). However, little has been said about teacher´s educator’ learning in this context. Thus, in this paper, I describe the general contributions of participating and writing about PIBID for my own personal development, as the very product of my participation in the program while articulating PIBID and Teaching practicum.